Nutshell [compact disc, unabridged] : a novel - McEwan, Ian (Recorded Books, 2016)
Trudy has betrayed her husband, John. She's still in the marital home--a dilapidated, priceless London townhouse--but John's not here. Instead, she's with his brother, the profoundly banal Claude, and the two of them have a plan. But there is a witness to their plot: the inquisitive, nine-month-old resident of Trudy's womb.